Coming death traces of mortality across East Asia. - RICHARD F. CALICHMAN (ALBANY : STATE UNIV OF NEW YORK PR, 2022)
Explores questions of death and mortality in several key texts of East Asian literature and cinema.
Lines of mortality in Kurosawa Akira's Ikiru -- Tsai Ming-liang and the Time of survival -- From culture to finitude : the question of Death in Takeuchi Yoshimi's reading of Lu Xun -- Interlacings of nothing : the question of death in Takeuchi Yoshimi's reading of Lu Xun II.
JSTOR
Keywords: Death in motion pictures; Mortality in motion pictures; Death in literature; Mortality in literature; East Asian literature -- History and criticism; Mort au cinéma.; Mortalité au cinéma.; Mort dans la littérature.; Mortalité dans la littérature.; Littérature extrême-orientale -- Histoire et critique